Rocket exhaust plume phenomenology - Simmons, Frederick S. (Aerospace Press ; American Institute of Aeronautics and Astronautics, 2000)
Annotation Presents an introductory treatment of plume phenomenology as it relates to the development of space-based defense systems. Covers elementary principles of rocketry, basics of rocket-propellant combustion, gas dynamics of supersonic exhaust plumes, infrared radiation processes, and diagnostic measurement techniques. Material is written at a level intended to bridge the gap between the needs of space systems engineers and the knowledge of scientists involved in detailed studies of plume observables. Simmons is a consultant in the private sector, and has been a consultant to Air Force space-based defense programs. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Gas dynamics.; Plumes (Fluid dynamics); Rocket engines -- Exhaust emissions.; Rockets (Aeronautics); elektronické knihy; electronic books